THE ROLE OF OPTICAL METHODS IN THE EVALUATION OF THE FUNCTIONING OF ROTARY INSTRUMENTS - PATIENT COMFORT BINOME DURING DENTAL TREATMENTS - Gabriel G. Condurache; Kamel Earar; Diana Elena Oiță; Costel Iulian Mocanu (Romanian Dental Association for Education, 2024)
Dentistry, particularly in recent decades, has also made important advances thanks to the knowledge of mechanical engineering. By combining knowledge from different practical fields but with common purposes, the dental instruments we see today in dental surgeries were developed. In the framework of research for the realization of this work, together with a team including dentists, an experimental stand was designed at the "Dunărea de Jos" University of Galati for the study of stress and deformation states in the masticatory system upon application of loads. In order to carry out the experiments, the printed PLA model had to be adequately prepared by painting with white matte paint. In order to be able to record the deformations during stress loading after painting with white paint, splashes of black paint (also matt) were applied. A surface to be studied is chosen to be followed by the 2 high resolution cameras of the ARAMIS HS system. The results obtained using optical methods are correlated with other applied methods, which are part of a much broader study represented by tensiometric methods, tests on the specimen made of PLA and tests on experimental modeling of mastication on the human bone specimen.